Answer:
False
Explanation:
Solving the equation
3x² - 5x - 2 = 0
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 3 × - 2 = - 6 and sum = - 5
The factors are - 6 and + 1
Use these factors to split the x- term
3x² - 6x + x - 2 = 0 ( factor the first/second and third/fourth terms )
3x(x - 2) + 1(x - 2) = 0 ← factor out (x - 2) from each term
(x - 2)(3x + 1) = 0
Equate each factor to zero and solve for x
x - 2 = 0 ⇒ x = 2
3x + 1 = 0 ⇒ 3x = - 1 ⇒ x = -
![(1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ykdkxxvb0vy4uekf2qgigigcflq5pi94b6.png)
Solutions are x = 2 and x = -
![(1)/(3)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/ykdkxxvb0vy4uekf2qgigigcflq5pi94b6.png)